Pengolahan Data Siswa SMA Negeri 1 Sambuara Kabupaten Kepulauan Talaud Pada Aplikasi DAPODIK: Data Processing of Students of SMA Negeri 1 Sambuara, Talaud Islands Regency in the DAPODIK Application - Oktavini Safitri Udang; Meike Tabaru; Eliyah Acantha Manapa Sampetoding; Esther Sanda Manapa (Jurnal Dynamic Saint, 2021)
SMA Negeri 1 Sambuara was founded based on the wishes of the community, in order to be able to present a high school education level (SMA) in Essang Selatan District, Talaud Islands Regency. Data processing is a complicated matter and must be meticulous. In this case the computer plays an important role as a tool in processing data. Processing student data at DAPODIK (Basic Education Data) to load data on education units, students, educators and education personnel, and educational substance whose data comes from educational units which are continuously updated online. To obtain valid data according to conditions in the field and to maintain data quality, three stages are arranged which are managed by different work units, namely the stages of collection, management and utilization. This research was conducted by means of observation, interviews, to obtain the profile of SMA Negeri 1 Sambuara in proposing functions and mechanisms for processing student data.